The Longman standard history of nineteenth century philosophy - Kolak, Daniel (Pearson/Longman, 2006)
Includes bibliographical references; 5 parts: The legacy of Kant: Avatar of nineteenth century philosophy; the german idealists; the existentialists; the social philosophers; the american pragmatists and idealists